La sociedad de hecho, su constitución legal y su incidencia en la sociedad ecuatoriana - Villarreal Abarca, Guillermo Enrique (2016)
This paper gives a brief overview of the legal principles established in the Constitution of the Republic of Ecuador, the Civil Code, Code of Civil Procedure regarding Ecuadorian Dissolution of Marriage Legislation in the Ecuadorian Society; is why in the development of this research has analyzed all that has to do with the de facto union: its history, constitutional development, the requirements for their existence and all that encompasses the legal treatment of company assets. The theme chosen for this thesis states: "THE SOCIETY IN FACT, HIS LEGAL CONSTITUTION AND ITS IMPACT ON THE ECUADORIAN SOCIETY"; the same were raised objective ¨Make a law firm with respect to the property regime and the state of legal uncertainty cohabiting common-law because of the absence of a legal provision concerning cohabiting common-law regarding the management of heritage have¨ Similarly, the hypothesis states: ¨The lack of anticipation of legal regulations regarding the management of property incurred during the union, left in a total state of legal uncertainty cohabitants, because the absence of any specific limitation and to record the social good the name of one of the cohabitants, this may alienate freely in any moment.¨ To get to check each of these expressions, I conducted a literature which was the basis for the field research itself in the opinion of lawyers of those who obtained it was established in conclusion that the present procedure to provide for finished violent union rights made one spouse , causing serious damage socially and economically. It is established so that research framed in a deep doctrinal legal analysis has validity and reliability criteria lawyers professionals with vast experience provided me, to finally present the conclusions, recommendations and legal reform of the Civil Code, I propose as an alternative solution to this problem.